Lactation in Al-Quran Perspective - Nanang Rokhman Saleh (Universitas Nahdlatul Ulama Surabaya, 2012)
One of the provisions of law which has been described in the Qur'an is the problem radha'ah (feeding) or lactation. The word of Radha'ah in the Qur’an is used for two meaning: first, as one reason for marriage forbidden due to foster sister (QS. al-Nisa’: 23), and second, as the activity of breastfeeding for the mother to her baby, in which the milk becomes the main food for babies, especially the first six months of birth, and highly recommended it be given to infants until two years old (Surah al-Baqarah: 233). Feeding activity is a series of pregnancy, childbirth and infant care. The fourth activity has been established by Allah to each of women as the nature and the trust as well. All of these gifts, recognized by the Qur'an as a condition that is very exhausting and burdensome to mother, but noble in the sight of Allah. Therefore, children must be grateful, respectful and dutiful to his parents, so that they can remember the good, service, and the struggle of his parents (Luqman: 14, al-Ahqaf: 15) Radha'ah as the main activity of the mother after the birth of her baby, bring benefits to both mother and baby. Breastfeeding can build psychological situation of calm and full of affection between mother and child. However, in practice, interest of mother in giving breastfeed declined, whereas the Qur’an has set the terms of breastfeeding, obligations and rights of mothers to breastfeed, breastfeeding and weaning time limit. The father should provide to mother during breastfeeding or find a woman to give breastfeeding and these conditions causes mahram. In addition, breast-feeding should be intended for the worship of Allah so the mother had the pleasure and reward from Him.